EFFECTS OF DRYING METHODS AND SOLVENTS ON PHENOLIC AND FLAVONOIDS CONTENT, DPPH RADICAL SCAVENGING AND -GLUCOSIDASE ACTIVITIES OF Aquilaria LEAVES EXTRACT - WAN-NADILAH, WAN AHMAD; GHANI, DAILAMI ABDUL; ABD JALIL, MUHAMMAD SYAFIQ; ALI, ABDUL MANAF; MAMAT, WAN NUR AMALINA WAN; MAHMOD, NOR HASIMA (Malaysian Applied Biology, 2020)
Aquilaria is a multipurpose plant with high commercial and medicinal values. The present study aimed to evaluate the effects of drying methods and extraction solvents on the phenolic and flavonoids content in A. malaccensis (AMA), A. subintegra (ASU), and A. sinensis (ASI). Leaf samples were either Air-Dried (AD) or Oven-Dried (OD) and extracted using 100% Ethanol (EE100), 70% ethanol (EE70), aqueous (AE), and hexane (HE). There was a significant difference (p<0.05) between the drying methods and the extracting solvents. The OD in AMA leaf samples gave the highest values of total phenolic compounds (TPC) (52.98 – 85.15 mg GAE/gm) and total flavonoid compounds (TFC) (2180.97 – 3733.45 QUE ppm). The highest DPPH radical scavenging was observed in OD-EE70-AMA with the IC50 value of 33.60 µg/mL. Meanwhile, OD-EE100-AMA gave the lowest IC50 value (0.13 µg/mL) in the a-glucosidase assay, followed by OD-EE70-AMA with IC50 value 0.69 µg/mL with no significant differences among them. OD-EE70-AMA was found to have a higher content of TPC and TFC with the most potent DPPH scavenging and a-glucosidase inhibition activities. A strong positive correlation was reported between bioassays and TPC or TFC, hence indicating that AMA leaf used in this study might have the potential as a natural antioxidant and an antidiabetic agent.